Risk factors associated with the presence of fatigued pigs during transport and their implications on high pH in muscle - Romero, Marlyn Hellen (2018)
The aim of this study was to determine the transport risk factors associated with the presence of fatigued pigs and its implications on high muscle pH in market-weight pigs. A case-control study was conducted, including 94 fatigued pigs as case and 94 typical pigs as controls. Pigs used in this study were castrated males and young females of a commercial genotype and standard market weight (mean BW 115.5 ± 1.3 kg) castrated and gilts of a standard commercial genotype. Structured face-to-face questionnaires were applied to characterize the transport conditions, and pH45 and pH24 carcass were evaluated. The logistic regression model showed that numbers of decks, the presence of assistant, sex, and transport speed and time were variables associated with the presence of fatigued pigs. Fatigued pigs had more probability of high muscular pH than typicalpigs (p<0.01). These results indicate that the transport is a stress factor for pigs with implications on the presence of fatigued pigs and meat with high pH24.